Anti-microbial Antibodies, Host Immunity, and Autoimmune Disease - Peilin Zhang; Lawrence M. Minardi; J. Todd Kuenstner; Steven M. Zekan; Rusty Kruzelock (Frontiers in Medicine, 2018)
Autoimmune diseases are a spectrum of clinical inflammatory syndromes with circulating autoantibodies. Autoimmune diseases affect millions of patients worldwide with enormous costs to patients and society. The diagnosis of autoimmune diseases relies on the presence of autoantibodies and the treatment strategy is to suppress the immune system using specific or non-specific immunosuppressive agents. The discovery of anti-microbial antibodies in the blood of patients with Crohn's disease and Sjogren's syndrome and cross-reactivity of anti-microbial antibodies to human tissue suggests a new molecular mechanism of pathogenesis, raising the possibility of designing a new therapeutic strategy for these patients. The presence of anti-microbial antibodies indicates the failure of the innate immunity system to clear the microbial agents from the blood and activation of adaptive immunity through B-lymphocytes/plasma cells. More importantly, the specific antibodies against the microbial proteins are directed toward the commensal microbes commonly present on the surface of the human host, and these commensal microbes are important in shaping the development of the immune system and in maintaining the interaction between the human host and the environment. Persistence of these anti-microbial antibodies in patients but not in normal healthy individuals suggests abnormal interaction between the human host and the commensal microbes in the body. Elimination of the organism/organisms that elicits the antibody response would be a new avenue of therapy to investigate in patients with autoimmune diseases.